DROPOUT OF INFERTILITY TREATMENTS AND RELATED REASONS / FACTORS : A SYSTEMATIC REVIEW - Syahputra Damanik, Roni Andre (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Infertility is a somewhat frequent disorder that can have a variety of causes, including those related to the woman, the man, or both. There is no recognized cause of infertility. The problem of infertility may have a significant impact on married couples who encounter it, including physical, economic, and psychological concerns as well as impacts on the couple's ability to have children. Infertile couples are typically subjected to a lengthy process of diagnosis and therapy, which can be both a psychological and a physical strain on the couple's lives. The reasons and drivers of couple-focused dropout are unclear. Many couples benefit from dropping out. At least one IVF cycle can be a "ritual" in the mourning process of childlessness, a self-imposed act to avoid regretting "not having tried everything to have a child." Current literature lacks this technique. It's possible for partners in a relationship to decide to end their participation in treatment for a number of different reasons, including mental and physical anguish, financial restrictions, or a bleak prognosis. It would appear that educational and support programs on psychological, economic, therapeutic, demographic, and personal issues could be helpful in reducing the number of people who stop going through with their infertility treatment before it is finished. These programs could focus on any of the following areas: infertility, treatment, people, or demographics.